A Strategy for the Long War: The Key Components of Counterinsurgency fro Malaya and the Philippines - Bjorklund, Eric R. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This paper examines the counterinsurgency strategies implemented by the British during the Malayan emergency from 1948-1960 and the Philippine's during the Hukbalahap Rebellion from 1946-1954 in order to determine a set of key components that compromise successful counterinsurgency strategy. The purpose of the paper is to inform policymakers and military leaders of the complexities of counterinsurgency, yet provide a framework for developing a robust counterinsurgency strategy that transcends time and geographic location. Given the increased threat from asymmetric, irregular enemies, this paper is an attempt to better prepare the U.S. for these relevant, dangerous threats. This examination is developed in three parts. First, in order to develope a framework for defeating insurgency, an understanding of insurgency strategy is necessary. Second, historic counterinsurgency doctrine is analyzed in order to determine the most essential components of successful strategy. In this section, four key components of counterinsurgency are developed. First, the population must always be defined as the center of gravity. Second, dynamic leadership is a critical element. Third, a government must defedine its national and military strategy to counter the asymmetric threat. Fourth, a government must be capable of altering the structure of its military forces away from conventional war models. The final selection utilizes case study methodology to analyze the two successful counterinsurgency operations based on the key components developed earlier in the paper.